2020
DOI: 10.3390/jcm9030747
|View full text |Cite
|
Sign up to set email alerts
|

Breast-Specific Gamma Imaging with [99mTc]Tc-Sestamibi: An In Vivo Analysis for Early Identification of Breast Cancer Lesions Expressing Bone Biomarkers

Abstract: The main purpose of this pilot investigation was to evaluate the possible relationship among [99mTc]Tc-Sestamibi uptake, the presence of breast osteoblast-like cells, and the expression of molecules involved in bone metabolism, such as estrogen receptor, bone morphogenetic proteins-2, and PTX3. To this end, forty consecutive breast cancer patients who underwent both breast-specific gamma imaging with [99mTc]Tc-Sestamibi and breast bioptic procedure were retrospectively enrolled. From each diagnostic paraffin b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In the future, these protocols could be used to develop diagnostic investigations based on nuclear medicine studies. In our previous study, we used similar approaches to find possible in vivo imaging markers to discriminate the breast cancer characterized by the presence of BOLCs and microcalcifications to those without them [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…In the future, these protocols could be used to develop diagnostic investigations based on nuclear medicine studies. In our previous study, we used similar approaches to find possible in vivo imaging markers to discriminate the breast cancer characterized by the presence of BOLCs and microcalcifications to those without them [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed a significant positive association among the sestamibi uptake and the proliferation index evaluated both in terms of the number of Ki67 positive cells and mitosis. This can be explained by (1) the capability of sestamibi to remain in the mitochondria after passive diffusion [ 14 ], (2) the increased uptake of sestamibi in mitochondria with high membrane potential [ 12 ], and (3) the role of mitochondria and their membrane potential in the cell proliferation process [ 25 ]. Of note, we also found that age affects neither the sestamibi uptake nor proliferation index in our case selection.…”
Section: Discussionmentioning
confidence: 99%
“…Irregular-shaped regions of interest (ROIs) were used to encase the lesions. The evaluation of the lesion to nonlesion ratio (L/N) was estimated according to our previous study [ 12 ]. For the patients who underwent [ 99 mTc]Sestamibi SPECT before biopsy (n = 15), the [ 99 mTc]Sestamibi SPECT-guided biopsy procedure was performed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations